Financial Distress in Textile and Garment Companies: The Influence of Financial Performance, Firm Size, and Good Corporate Governance - Fidelya Meindra Shafitri; Wiwin Aminah (LP2M IAIN Palopo, 2026)
The textile and garment industry plays an important role in Indonesia’s economy but faces financial pressures that may increase the risk of financial distress. This study aims to examine the effects of financial performance, firm size, and good corporate governance on financial distress in textile and garment companies listed on the Indonesia Stock Exchange during 2020–2024. Using a quantitative explanatory design, this study analyzed secondary data from 13 companies, resulting in 65 firm-year observations. Financial distress was measured using the Altman Z-Score, while financial performance, firm size, and corporate governance were measured by ROA, natural logarithm of total assets, board of directors, and board of commissioners, respectively. Panel data regression was conducted using EViews 13. The results show that ROA, firm size, and board of directors have no significant effect on financial distress, while the board of commissioners has a positive and significant effect on the Altman Z-Score. Simultaneously, all independent variables significantly affect financial distress. These findings highlight the importance of effective board supervision in strengthening corporate financial resilience.